Genetic studies of yield and quality traits in aromatic rice genotypes through Hayman’s approach - Bano, Dilruba A; Singh, S P (ORYZA-An International Journal of Rice, 2019)
Hayman’s approach analysis was employed to estimate genetic components of variation in aromatic rice genotypesÂ for yield and quality traits by following 8 x 8 one way diallel mating design. Vr-Wr graphs were plotted for theÂ traits viz., days to 50 % flowering, days to maturity, plant height at maturity, main panicle length, effective tillersÂ per plants, 100 grain weight and yield per plant, that exhibited significant deviation of regression coefficient ’b’Â from zero, irrespective of significance of ’t2’ or deviation of ’b’ from unity. Vr-Wr graph revealed over dominanceÂ for the traits viz., plant height, main panicle length, effective tillers per plant and yield per plant. Traits like daysÂ to 50 % flowering, days to maturity and 100 grain weight revealed partial dominance. Graphical and componentÂ analysis revealed over dominance type of intra allelic interaction for most of the yield and yield contributingÂ traits. However, both additive and dominance types of genetic effects were observed for most of yield and quality traits.